2014
DOI: 10.3109/21691401.2014.965309
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone acetate–Eudragit® RS100 electrospuns: Preparation and physicochemical characterization

Abstract: The aim of the present study was to formulate methylprednisolone acetate -Eudragit(®) RS100 nanofibers and nanobeads by the electrospinning method. The physicochemical characteristics of the prepared electrospuns were assessed as well. The particle size and morphology were evaluated using scanning electron microscopy. The crystallinity of the drug in the nanofibers and nanobeads obtained was also studied by X-ray crystallography and differential scanning calorimetry (DSC) thermograms. In addition, FT-IR spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…HCl during the electrospraying procedure. These findings were in good agreement with DSC thermograms and similar previously reported results for the TA-PLGA, AZI-PLGA and MPA-Eud electrosprayed nanobeads [22][23][24].…”
Section: Dsc Evaluationsupporting
confidence: 93%
See 4 more Smart Citations
“…HCl during the electrospraying procedure. These findings were in good agreement with DSC thermograms and similar previously reported results for the TA-PLGA, AZI-PLGA and MPA-Eud electrosprayed nanobeads [22][23][24].…”
Section: Dsc Evaluationsupporting
confidence: 93%
“…It can be concluded that the beads formation occurs in the low concentration of solutions (1:5 and 1:10 drug:polymer ratios). The solution at the low polymer concentrations has high surface tension which leads to the dispersion of liquid jet into the divided droplets; on the contrary, the fibre formation could be dominated at the high polymer concentrations because of the increasing in the viscoelastic forces [12,[22][23][24][37][38][39]. So, therefore, the formation of fibres or beads was highly affected by polymer solution concentrations; where the size of the prepared beads is increased by increasing the solution concentration and the fibres were produced at the highest solution concentration.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations